Inhibition of platelet aggregation by activation of platelet intermediate conductance Ca2+‐activated potassium channels. (7th August 2022) - Back, Valentina; Asgari, Amir; Franczak, Aleksandra; Saito, Max; Castaneda Zaragoza, Diego; Sandow, Shaun L.; Plane, Frances; Jurasz, Paul
Abstract: Background: Within the vasculature platelets and endothelial cells play crucial roles in hemostasis and thrombosis. Platelets, like endothelial cells, possess intermediate conductance Ca 2+ ‐activated K + (IKCa ) channels and generate nitric oxide (NO). Although NO limits platelet aggregation, the role of IKCa channels in platelet function and NO generation has not yet been explored. Objectives: We investigated whether IKCa channel activation inhibits platelet aggregation, and per endothelial cells, enhances platelet NO production. Methods: Platelets were isolated from human volunteers. Aggregometry, confocal microscopy, and a novel flow chamber model, the Quartz Crystal Microbalance (QCM) were used to assess platelet function. Flow cytometry was used to measure platelet NO production, calcium signaling, membrane potential, integrin αIIb /β3 activation, granule release, and procoagulant platelet formation. Results: Platelet IKCa channel activation with SKA‐31 inhibited aggregation in a concentration‐dependent manner, an effect reversed by the selective IKCa channel blocker TRAM‐34. The QCM model along with confocal microscopy demonstrated that SKA‐31 inhibited platelet aggregation under flow conditions. Surprisingly, IKCa activation by SKA‐31 inhibited platelet NO generation, but this could be explained by a concomitant reduction in platelet calcium signaling. IKCa activation by SKA‐31 also inhibited dense and alpha‐granule secretion and integrin αIIb /β3 activation, but maintained platelet phosphatidylserine surface exposure as a measure of procoagulant response. Conclusions: Platelet IKCa channel activation inhibits aggregation by reducing calcium‐signaling and granule secretion, but not by enhancing platelet NO generation. IKCa channels may be novel targets for the development of antiplatelet drugs that limit atherothrombosis, but not coagulation.